Pengaruh Game Online Mobile Legends Terhadap Perilaku Bahasa Pada Gen Z Di Sidoarjo - Zabrina Fitri Novi Amanda; Robby Firdaus Rachman; Hesti Kartika Sari; Tarsianus Jebarus; Eni Nurhayati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Technological developments have brought significant changes in lifestyle, especially among Generation Z (Gen Z). One phenomenon is the popularity of online games such as Mobile Legends. This research aims to investigate the influence of the intensity of playing Mobile Legends on the language behavior of Gen Z. In this research, the author used a descriptive study research method with a quantitative approach, and used a Google Form questionnaire as a data collection medium. This research involved an online survey of teenagers aged 11 to 26 years using Google Form which was distributed using social media. The research results show that the Mobile Legends game has a significant impact on various aspects of teenagers' lives, including physical responses, body movements, facial expressions, imitation of character movements, and use of typical terms.